Florida Solid and Hazardous Waste Regulation Handbook: Federal Agencies - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
There are four federal agencies that regulate solid and hazardous waste: The Environmental Protection Agency (EPA),  The United States Coast Guard (USCG), The Army Corps of Engineers (ACOE), and The Department of Transportation (DOT). This is EDIS document FE453, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.